American Humor used in an American Comedy Movie The Boss - Sastika Seli; Bahya Alfitri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The research aims to describe the functions of humor used in an American comedy movie The Boss. The subject of the research was American comedy movie The Boss. Descriptive qualitative method was used to conduct the research. Data collection was done through library research and documentation. Data analysis was done through identification, coding, classification and description. The researcher found several findings. Supported by Meyers theory of joke, there are 6 functions of jokes found in the movie such as to insult someone, to express anger, to tease someone, to relieve tension, to get attention, and to amuse others. The dominant function was differentiation particularly to insult and to express anger 21 times, the second was clarification particularly to relieve tension humorous lines and amuse others 15 times, the third was enforcement particularly to tease 18 times, and the last was identification particularly to relieve tension and to get attention 27 times. These functions were also analyzed and discriminated by different setting and participant based on formality and participants distance. According to the analysis, most jokes occurred in informal situation with intimate relationship among the participants and functioned to tease someone and to relieve tension. This finding also proves that American humor is expressed with more slapstick and vulgarity as the characteristic of American humor used in daily communication. Keywords: sociolinguistics, humor, American humor, American comedy movie, The Boss movie